Growth mechanism of porous 3C–SiC films prepared via laser chemical vapor deposition. Issue 10 (July 2020) - Cai, Liuyi; Xu, Qingfang; Lu, Wenzhong; Tu, Rong; Goto, Takashi; Zhang, Song
Abstract: Porous SiC film is an excellent electrode material for robust micro-supercapacitors used in extremely harsh environments. In one of our previous studies, porous 3C–SiC film with high areal capacitance and high deposition rate was prepared via laser chemical vapor deposition (LCVD). However, it is still urgent to explore the formation mechanism of porous structures using LCVD. In this study, the microstructure of the porous cubic SiC film prepared via LCVD was analyzed in detail using scanning and transmission electron microscopy techniques. The growth mechanism of the deposits has been proposed according to the "growth competing theory" and "shadow effect theory."